Meningkatkan Scientific Writing Skill Siswa pada Pembelajaran Biologi Kelas X MIA 7 SMA N 4 Surakarta Menggunakan Guided Inquiry Learning Dipadu Reading Assignment - DISPRIYANI, NOVITA; RAMLI, MURNI; Nurmiyati, Nurmiyati; SUMARJIYANA, TUTUT (Bioedukasi: Jurnal Pendidikan Biologi, 2015)
This research aims to enhance Scientific Writing Skill (SWS) of students on biology through the application of guided inquiry learning with reading assignment. This research was a three cycles Classroom Action Research (CAR). Each cycle consisted of four phases, i.e. planning, acting, observing, and reflecting. The subjects of this research were 30 students of Grade X MIA 7 of SMA N 4 Surakarta, consists of 11 male and 19 female students. Lesson plan of ecosystem were designed for three sub topics, i.e. Component of ecosystem and its interaction; Food chain and food web; and the last sub topic was biogeochemical cycles. The assessment were analyzed using scientific writing skill’s rubric adapted from Toppen (2014), which will measure the ability to develop writing creatively, use spelling and grammar correctly, communicate knowledge which construct and connect science and technology with the real world. The result of this research was guided inquiry learning had effectively increased student’s SWS. The average percentage increased from 38,13 % in pre-cycle to 77,29 % in third cycle, and the skills of students increased about 12.87% after the treatment on each cycle.